2020
DOI: 10.1007/s00198-020-05718-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cancer surveillance: results from the Forteo Patient Registry Surveillance Study

Abstract: The Forteo Patient Registry estimated the incidence of osteosarcoma in US patients treated with teriparatide and enrolled in the study between 2009 and 2019. No incident cases of osteosarcoma were identified among patients registered, and the crude incidence rate was 0 (95% confidence interval [CI], 0-10.2) cases per million person-years. Purpose The prospective, voluntary Forteo Patient Registry was established to estimate the incidence of osteosarcoma in patients who have received treatment with teriparatide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…In male and female rats, teriparatide caused an increase in the incidence of osteosarcoma (a malignant bone tumor) that was dependent on dose and treatment duration. The effect was observed at systemic exposures to teriparatide ranging from 3 to 60 times did not show an increase in risk of OS in humans (7,38,39,41,42) Warnings and precautions (osteosarcoma) In male and female rats, teriparatide caused an increase in the incidence of OS (a malignant bone tumor) that was dependent on dose and treatment duration. Teriparatide should not be prescribed for patients with increased baseline risk of OS.…”
Section: Boxed Warningmentioning
confidence: 97%
See 2 more Smart Citations
“…In male and female rats, teriparatide caused an increase in the incidence of osteosarcoma (a malignant bone tumor) that was dependent on dose and treatment duration. The effect was observed at systemic exposures to teriparatide ranging from 3 to 60 times did not show an increase in risk of OS in humans (7,38,39,41,42) Warnings and precautions (osteosarcoma) In male and female rats, teriparatide caused an increase in the incidence of OS (a malignant bone tumor) that was dependent on dose and treatment duration. Teriparatide should not be prescribed for patients with increased baseline risk of OS.…”
Section: Boxed Warningmentioning
confidence: 97%
“…Limitations of this study were that the study was not comparative and the number of patients enrolled was lower than the target number to evaluate the risk of developing osteosarcoma. (41) Although these earlier studies did not suggest an increased risk of osteosarcoma in patients treated with teriparatide, they were inadequate to sufficiently characterize osteosarcoma risk. Accordingly, two large, population-based, observational cohort studies were undertaken to identify a larger sample of patients treated with teriparatide using Medicare and a large commercial claims database.…”
Section: Postmarketing Surveillance Studies: Incidence Of Osteosarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…11 The recombinant human PTH analog teriparatide was approved in 2002 by the US Food and Drug Administration (FDA) for the treatment of osteoporosis at high risk for fracture and increased bone mass in postmenopausal women. 12 This drug has been demonstrated to promote bone healing and prevent fragility fractures in both rats and humans. 13,14 In addition to its numerous clinical advantages, teriparatide has some less well-known contraindications, such as a history of radiation therapy, 15 the presence of primary malignant and metastatic bone tumors, 7,16 and Paget's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a 15-year post-marketing surveillance study and Forteo Patient Registry Surveillance study demonstrated that the incidence of osteosarcoma associated with teriparatide use was no different than would be expected based on the background incidence rate of osteosarcoma. [ 132 , 133 ] Moreover, a recent study demonstrated the effectiveness of teriparatide for MRONJ in malignant bone disease patients [ 130 ] that might contribute to changing labels with further evidence.…”
Section: Medical Management Of Patients With Mronjmentioning
confidence: 99%